Long-term results after surgical treatment in patients suffering from chronic pancreatitis with signs of biliary hypertension - Pylypchuk, V. I. (Zaporozhye Medical Journal, 2018)
The morbidity of chronic pancreatitis (CP) remains at a high level. Over the past thirty years, more than doubled growth in the number of patients with chronic pancreatitis has been noted. Objective of our work is to study the long-term results after surgical treatment in patients suffering from CP with signs of biliary hypertension (BH) in order to justify adequate approaches to surgical treatment. Materials and methods. The long-term results after surgical treatment in 163 patients suffering from CP with signs of BH were analyzed. The patients were divided into two groups: the group 1 (main) – 36 (22.1 %) patients, who underwent intraoperative monitoring of biliary pressure (IOM BP) for BH diagnostics; the group 2 (comparison group) – 127 (77.9 %) patients, who underwent common methods. Results. Resection, drainage and palliative operations were performed in patients with CP and BH: resection surgeries – 95 (58.3 %) patients; draining surgeries – 44 (26.9 %) patients; palliative surgeries – 24 (14.8 %) patients. The long-term quality of life study after surgical interventions was conducted in 94 (57.6 %) patients. Good results were obtained in 25 (89.2 %) patients of the group 1 and in 45 (68.2 %) patients of the group 2; satisfactory – in 2 (7.1%) patients of the group 1 and in 17 (25.7 %) patients of the group 2; unsatisfactory – in 1 (3.6 %) patient of the group 1 and in 4 (6.1 %) patients of the group 2. Conclusions. The proposed comprehensive diagnostic-therapeutic approach using the IOM BP method allowed obtaining good long-term results in 89.2 % of patients in the absence of BH recurrence. In the group of patients without BP monitoring the recurrent BH with mechanical jaundice manifestations appears significantly more often by 15.1 % (χ2 = 4.22, P = 0.04).